Virtuous acts in the midst of war (2014)
War not only destroys life; it alsodrains the moral reserves of bothcombatants and those promotingthe confrontation. In the midst ofthe ethical disaster in Colombia,some persons and communitieshave reminded us of the importanceof virtuous actions.